Medial‐to‐lateral plantar loop technique for retrograde transcollateral recanalization of the lateral plantar artery in patients with type 3 plantar arch. Issue 6 (31st August 2020) - Testi, Gabriele; Ceccacci, Tanja; Maioli, Filippo; Grotti, Simone
Abstract: A 89‐year‐old male presented with severe untreatable pain and ischemic non‐healing ulcer in the left forefoot. The pre‐procedural angiograms showed multiple stenosis of the superficial femoral and popliteal arteries, occlusion of anterior tibial artery, tibio‐peroneal trunk (TTP) and distal posterior tibial artery (PTA), stenosis of the peroneal artery, and the patency of the medial plantar artery (MPA) as a single pedal artery, with very poor perfusion of the lateral aspect of the forefoot. The TTP and PTA were recanalized, and balloon angioplasty of superficial femoral artery and popliteal artery and peroneal artery was carried out. After unsuccessful antegrade attempts, the lateral plantar artery (LPA) was retrogradely recanalized performing the medial‐to‐lateral plantar loop, navigating from the deep branch of MPA to the plantar arch and reentering back in the common plantar artery through the LPA. Balloon angioplasty of LPA was performed though the retrograde and antegrade route. When the MPA is the single pedal artery, and the antegrade recanalization of the dorsalis pedis artery (DPA) and the LPA is not possible, the medial‐to‐lateral plantar loop is a feasible technique to recanalize the LPA retrogradely through the plantar arch.